Study of some thermal properties and activation energy of epoxy resin alloys with copper complex of acid N, N-5,2-toluene di-malic acid - Iptihag Al-Halim; Akram Mohammed (College of Education for Pure Sciences, 2013)
ABSTRACT Research includes the study of thermal isothermal Epoxy resin alloy with copper complex,( N,N - 2,5 Tolylene  bismaleamic acid Copper (2,5TBMA Cu), through thermal analysis measurements weighted at temperature constant time it takes to reach the constant weight within 23 minutes compared to 17 minutes for the epoxy alone. It has been treated at temperatures, was a high values ​​end CDT decomposition and a percentage values ​​weighted 350 (% Wt) whenever the temperature increased treatment .When treatment had employed resulted to a higher values ​​of the weighted at 350 C°  (Wt%)350 in the middle neutral. Fuoss equation had been used to calculate the activation energy for the beginning of the process of disintegration polymeric material.